C. Vann Woodward : America's historian - Cobb, James C. (James Charles), 1947- (Chapel Hill : The University of North Carolina Press, 2022)
"With an epic career that spanned two-thirds of the twentieth century, C. Vann Woodward (1908-1999) was a historian of singular importance. A brilliant writer, his work captivated both academic and public audiences. He also figured prominently in the major intellectual conflicts between left and right during the last half of the twentieth century, although his unwavering commitment to free speech and racial integration that affirmed his liberalism in the 1950s struck some as emblematic of his growing conservatism by the 1990s."--
The legendary historian -- Another Mark Twain if he applied himself: the superintendent's son spreads his wings -- A Southern historian I must be -- or somehow become: a budding biographer makes hard choices -- History, I find, is a collection of facts: pursuing the "cursed degree" in Chapel Hill -- A better read than Huxley's new novel: telling the Tom Watson story -- A chance to have my say about the period: the origins of "Origins" -- Juleps for the few and pellagra for the crew: reckoning with the redeemer -- New South legacy -- Cordially invited to be absent: integrating the Southern Historical Association -- A fundamental attack upon the prevailing view: launching "The strange career of Jim Crow" -- Wrong in all its major parts: "Strange career" returns to Earth -- A basis for criticizing the American legend: Southern history as both asset and burden -- Tortured for months: the agony of moving to Yale -- Therapist of the public mind: the strange career of C. Vann Woodward -- I mean to do all I can: the mentor flexes his muscles -- An ever more conservative old liberal: moving to the right or standing fast? -- I do not see how I could have been misunderstood: sorting out the Aptheker debacle -- The masterpiece that became a hoax (and won a Pulitzer): rewriting Mary Chesnut's diary -- Still more that I can do: the satisfactions of staying the course -- America's historian.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Woodward, C. Vann -- 1908-1999.; Woodward, C. Vann -- 1908-1999; Historians -- United States -- Biography; Southern States -- Historiography; Historiens -- États-Unis -- Biographies; États-Unis (Sud) -- Historiographie; BIOGRAPHY & AUTOBIOGRAPHY / Historical; Historians; Historiography; Southern States; United States; Biographies